Analysis of Corn Productivity Using the Objective Matrix (OMAX) Method (Case Study of PT. Santosa Utama Lestari) - Muhammad Anis Abqory; Devi Tanggasari (Protech Biosystems Journal, 2023)
Corn production at PT Santosa Utama Lestari has increased and decreased erratically, several factors can affect corn productivity such as the occurrence of downtime on machines, even in the rainy season sometimes corn production does not reach the production target. Productivity measurement can be done with several methods, one of which is the Objective Matrix (OMAX) method. The purpose of this research is to determine the level of productivity in the production section at PT Santosa Utama Lestari and to provide recommendations for improving productivity in the production section of PT Santosa Utama Lestari. Productivity at PT Santosa Utama Lestari tends to fluctuate. The highest total productivity was achieved in April 2022 with a value of 1000, the lowest total productivity occurred in August 2022 with a value of 25. To improve productivity PT Santosa Utama Lestari needs to improve the quality and availability of raw materials, motivate workers and provide adequate rest time, carry out machine maintenance, and carry out supervision of the use of electricity. The improvement recommendations obtained are that the company needs to increase the amount of raw materials to 4890.01 tonnes, a workforce of 11 people, machine working hours 214.04 hours and 54.32 Kwh of electrical energy.